2022
DOI: 10.1007/s11356-022-19118-w
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin protects against Cr(VI)-induced oxidative stress-associated hepatotoxicity by mediating the Akt-Keap1-Nrf2 signaling pathway

Abstract: Hexavalent chromium [Cr(VI)] is a serious environmental pollutant and threatens human health. Although it has been con rmed that oxidative stress is the main mechanism of liver injury caused by Cr(VI) exposure, the related toxic target and effective intervention measures have not been found. Clusterin (CLU) is an acute phase response protein with cytoprotective and apoptosis delaying effects, and its expression has been con rmed to increase signi cantly after exposure to Cr(VI). In this study, we demonstrate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Cr(VI)-induced oxidative stress is accompanied by damage to hepatocyte cell membranes, after which aminotransferases enter the blood plasma (Hassan et al, 2019). Therefore, changes in blood aminotransferases activity are an important indicator of the structural and functional state of the liver (Ma et al, 2022). We only observed a tendency to increase in ALT, AST activity in the blood plasma of rats of group IV relative to group III.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Cr(VI)-induced oxidative stress is accompanied by damage to hepatocyte cell membranes, after which aminotransferases enter the blood plasma (Hassan et al, 2019). Therefore, changes in blood aminotransferases activity are an important indicator of the structural and functional state of the liver (Ma et al, 2022). We only observed a tendency to increase in ALT, AST activity in the blood plasma of rats of group IV relative to group III.…”
Section: Resultsmentioning
confidence: 58%
“…Literature sources also indicate that Cr(VI)induced inflammatory processes in the liver and kidneys leads to a decrease in De Ritis ratio due to accumulation of ALT in blood plasma. Experimental data indicate that moderate and severe liver damage is characterized by de Ritis coefficients <1.0 (Ma et al, 2022;Buchko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The levels of lipid peroxidation and protein carbonyl group content in mice exposed to hexavalent chromium (Cr(VI)) were increased, and a large number of ROS were produced in the body. At the same time, the activities of SOD, glutathione S-transferase, GSH, total mercaptan (TT), CAT, and cholinesterase were decreased, which induced oxidative stress leading to liver cell damage, causing the increase of aspartate aminotransferase and alanine aminotransferase [ 79 ].…”
Section: Major Toxicity Mechanisms Induced By Mycotoxins and Heavy Me...mentioning
confidence: 99%
“…As Nrf2 has already been reported to regulate HO-1 expression (an antioxidant enzyme), the authors decided to focus their interest on this transcription factor. They demonstrated that the increase in Nrf2 is coordinated with a Cr(VI)-dependent induction of HO-1 via the Akt pathway [128].…”
Section: Nuclear Factor E2-related Factor 2 (Nrf2)mentioning
confidence: 99%